Unraveling the web of defense: the crucial role of polysaccharides in immunity - Shen, Yu; Zhao, Hongbo; Wang, Xuefeng; Wu, Shihao; Wang, Yuliang; Wang, Chaoxing; Zhang, Yu; Zhao, Hong (Frontiers in Immunology, 2024)
The great potential of polysaccharides in immunological regulation has recently been highlighted in pharmacological and clinical studies. Polysaccharides can trigger immunostimulatory responses through molecular identification, intra- and intercellular communication via direct or indirect interactions with the immune system. Various immunostimulatory polysaccharides or their derivative compounds interactsat cellular level to boost the immune system, including arabinogalactans, fucoidans, mannans, xylans, galactans, hyaluronans, fructans, pectin and arabinogalactans, etc. These natural polysaccharides are derived from various plants, animals and microbes. A unique structural diversity has been identified in polysaccharides, while monosaccharides and glucosidic bonds mainly confer diverse biological activities. These natural polysaccharides improve antioxidant capacity, reduce the production of pro-inflammatory mediators, strengthen the intestinal barrier, influence the composition of intestinal microbial populations and promote the synthesis of short-chain fatty acids. These natural polysaccharides are also known to reduce excessive inflammatory responses. It is crucial to develop polysaccharide-based immunomodulators that could be used to prevent or treat certain diseases. This review highlights the structural features, immunomodulatory properties, underlying immunomodulatory mechanisms of naturally occurring polysaccharides, and activities related to immune effects by elucidating a complex relationship between polysaccharides and immunity. In addition, the future of these molecules as potential immunomodulatory components that could transform pharmaceutical applications at clinical level will also be highlighted.